1991
DOI: 10.1002/ajh.2830360208
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin life span in rats with hypoplastic and hyperplastic bone marrows

Abstract: The metabolic fate of erythropoietin (EPO) remains unknown. Urinary excretion does not appear to play a major role and liver catabolism has been shown to occur only after terminal sugars on the hormone have been removed. However, it has been proposed that EPO is eliminated by consumption in the bone marrow. In order to examine the extent of such consumption we measured the half-life of radioidinated recombinant EPO injected intravenously (IV) to rats with bone marrows suppressed by cyclophosphamide or hypertra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
20
2

Year Published

1992
1992
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 24 publications
(12 reference statements)
4
20
2
Order By: Relevance
“…We further speculate that rapid expansion of erythroid precursors in the bone marrow at the time of the third EPO PK study contributed to the increase in EPO clearance and the shortening of EPO half-life. Clearly, future pre-and post-marrow ablative human studies are needed to confirm and extend these speculative statements extrapolated from pre-clinical studies in sheep.It should be noted that present findings, our previous PK report in busulfan-treated sheep, 18 and the findings of previous clinical studies noted above differ from those reported by Piroso et al 42 in rats. The latter authors observed that EPO clearance and half-life were not significantly altered by hypo or hyperplastic marrow states.…”
contrasting
confidence: 57%
See 2 more Smart Citations
“…We further speculate that rapid expansion of erythroid precursors in the bone marrow at the time of the third EPO PK study contributed to the increase in EPO clearance and the shortening of EPO half-life. Clearly, future pre-and post-marrow ablative human studies are needed to confirm and extend these speculative statements extrapolated from pre-clinical studies in sheep.It should be noted that present findings, our previous PK report in busulfan-treated sheep, 18 and the findings of previous clinical studies noted above differ from those reported by Piroso et al 42 in rats. The latter authors observed that EPO clearance and half-life were not significantly altered by hypo or hyperplastic marrow states.…”
contrasting
confidence: 57%
“…The latter authors observed that EPO clearance and half-life were not significantly altered by hypo or hyperplastic marrow states. 42 These authors used cyclophosphamide to induce marrow hypoplasia and phenylhydrazine or bleeding to induce marrow hyperplasia. It is possible that the extremely high EPO levels observed among the phenylhydrazine and phlebotomized groups of study animals (540 and 186 mU/mL respectively) had saturated EPO's nonlinear clearance mechanism, 6,43,44 thereby accounting for why Piroso et al 42 were not able to detect pre-and post-ablation differences in EPO PK.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum Epo concentration was used as the index of Epo production, because its rate of production is the main determinant of the serum level. 12 Parallel studies of renal Epo mRNA and plasma Epo 13 indicate that plasma hormone levels are a valid reflection of renal Epo production. Each subject granted informed written consent as approved by the University of Toronto Human Subjects Review Committee.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, after the conditions at the critmeter are changed to reduce the tissue oxygen pressure, the increased production of Epo requires gene transcription and protein synthesis, because there are no storage forms of Epo. 12,13 Furthermore, the 2-hour observation period may be inadequate to detect an effect of Ang II on Epo production. More recent data suggests that maximum changes in serum Epo are seen 24 hours following an appropriate stimulus.…”
mentioning
confidence: 99%